Effect of country governance on trade credit activities: Empirical evidence from Pakistan - Mosab I. Tabash; Umar Farooq; Basem Hamouri; Ashish Kumar; Mamdouh Abdulaziz Saleh Al-Faryan (Cogent Economics & Finance, 2023)
An existence of good governance situation ensures the progress of economic sectors. The recent literature has mentioned the role of country governance in multiple business operations. However, the effect of country governance on trade credit is not yet explored in the literature. Thus, the current analysis aims to test the empirical nexus between country governance and trade credit activities. The empirical analysis was arranged on Pakistani non-financial enterprises over the period 2010-2019. The regression between variables was established by employing the generalized least square and generalized method of the moment models. The empirical analysis documents the positive effect of aggregate governance index and other proxies of governance including voice and accountability, political stability, regulatory quality, and corruption control on both trade payables and receivables. The favorable governance situation makes business operations more transparent, reduces market uncertainty, and ensures the protection of rights. All these factors positively achieve trade credit operations. We find robust evidence in the presence of both firm-specific and macroeconomic factors. The findings of the study yield an important policy regarding the role of better governance in boosting trade-credit operations. By enlightening the direct effect of country governance on trade credit, this research adds the innovative arrangement of the variable in the existing literature.
Keywords: G32; G38; M48; 330; control of corruption; Country governance; political stability; trade-credit